Cognitive load detection of vision impaired in the inward places using Bio-signal - Kabir, Raiyan; Rashid, Md. Mamun Or (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.